Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Selective leaching of bastnaesite from mixed rare earth concentrate via fluidized oxidation roasting and AlCl3-assisted leaching: Facilitating synergistic REE-F leaching for efficient recovery - Rui Qu; Wenbo Li; Zaizheng Dong; Xue Bian; Maoyuan Wang; Linghui Zhang (Hydrometallurgy, 2026)

Biomass-derived Fe-HTC coupled with CuBi2O4 for photo-self-Fenton degradation and sterilization via in situ H2O2 generation and activation - Shuhao Zhang; Yiting lv; Jinjuan Xue; Rui Jing; Shuaishuai Ma; Mingxin Wang (Chemical Engineering Journal, 2026)

Planarization engineering of benzodithiophene-based nanogrids for enhanced carrier mobility and emission performance - Lei Yang; Jun Yang; Shi-rui Chen; Wen-bin Xie; Cong Sun; Wang-yang Wu; Xin-zhe Peng; Manas Ranjan Dash; Xue-qin Ran; Mohamad Akbar Ali; Ling-hai Xie (Chemical Engineering Journal, 2026)

Understory vegetation and soil microorganisms respond to afforestation on the Loess Plateau - Yunyin Xue; Ning Wang; Nan Gao; Lanxi Chen; Jun’e Liu; Rui Wang; Zhengchao Zhou (CATENA, 2026)

Iterative precursor rebalancing improves phenazine-1-carboxylic acid production in engineered Pseudomonas chlororaphis - Sheng-Jie Yue; Peng Huang; Chen Song; Song Li; Rui Lian Yao; Wei Wang; Xue-Hong Zhang; Pablo I. Nikel; Hong-Bo Hu (Bioresource Technology, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Accumulation of hydrophobic bile acids mediates chronic heat stress-induced liver-gut axis injury in spotted seabass (Lateolabrax maculatus) - Fan-bo Yang; Xue-shan Li; Kai Song; Ling Wang; Rui-juan Ma; Kang-le Lu; Chun-xiao Zhang (Aquaculture, 2026)

Occurrence, detection methods, and remediation technologies of per- and polyfluoroalkyl substances (PFAS) in soils - Yina Ma; Kang Lei; Shuwen Xue; Yong Wang; ShunHao Ai; Changjian Shang; Kunlong Hui; Ying Yuan; Rui Meng; Yuting Zhao (Process Safety and Environmental Protection, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

WaveUNet: An efficient deep network based on discrete wavelet transform and attention mechanism for InSAR phase unwrapping - Wenfei Mao; Hongquan Xiang; Xue Cheng; Guoxiang Liu; Xiaowen Wang; Rui Zhang; Oriol Monserrat; Michele Crosetto (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Thermal properties of lunar mantle olivine and constraints on the Moon's thermal asymmetry - Kewei Shen; Panming Xue; Duojun Wang; Rui Zhang; Guangchao Chen; Kexuan Zhang; Liang Wei (Icarus, 2026)

A novel physics-driven remeshing technique for particle finite element method - Wen-Rui Sun; Ke-Jian Wang; Wen-Qi Guan; Xue Li; Wei Zhang; Wei-Hai Yuan (Computers and Geotechnics, 2026)

Interface-engineered ZrO2@Co3O4 core-shell materials from bimetallic MOFs for enhanced room temperature NO2 sensing - Jiahui Fan; Xiaopeng Wang; Shanshan Cong; Rui Zhang; Weixin Lv; Li Li; Qingjiang Pan; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

Current-Time Typhoon-Induced Storm Surge Estimation at Lianyungang: A Fully Nested Event-Grouped Evaluation - Rui Liu; Dewei Wang; Shuaikang Zhao; Jierui Tang; Xue Li; Wenli Qiao (Journal of Marine Science and Engineering, 2026)
Storm surge current-time estimations are strongly influenced by recent water-level conditions, while the temporal dependence among samples from the same typhoon event can complicate the assessment of model generalization to unseen events. This study evaluated storm surge estimation at the Lianyungang tide gauge using 2168 samples from 28 typhoon events during 2002–2024. A 41-feature extreme gradient boosting (XGBoost) model integrating historical surge and physics-motivated information was evaluated using fully nested event-grouped cross-validation, with complete outer-test typhoon events excluded from hyperparameter optimization, early stopping, and model fitting. The 41-feature XGBoost model achieved a mean absolute error (MAE) of 0.083 m, a root mean square error (RMSE) of 0.128 m, and a coefficient of determination (R2) of 0.794. On the common valid sample subset, its RMSE was 9.15% lower than that of Persistence, and it achieved a lower event-level RMSE in 18 of the 28 independently held-out typhoon events. Controlled information-source experiments showed that historical surge information accounted for most of the aggregate predictive skill, whereas adding core storm-state variables and the complete set of physics-motivated descriptors produced only limited changes in overall performance. The relative improvement over Persistence was larger for samples in which the shortest available historical surge lag was 3–6 h than for those with a 1 h lag, but this advantage did not extend consistently to the highest-surge conditions, where systematic underestimation remained evident. These results demonstrate the importance of event-independent validation for assessing machine-learning storm surge estimation and show that the model skill depends strongly on both information availability and the surge magnitude. The framework should be interpreted as a retrospective, single-station current-time estimation approach rather than an operational forecasting or extreme-surge warning system.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

Groundwater-mediated controls and future projections of carbon stocks in coastal wetlands - Xulong Gong; Ying Liang; Xue Jiang; Rui Ma; Yuan Liu; Shun Hu; Yanxin Wang (Journal of Hydrology, 2026)

Initial exploration of the health effects on Qinghai-Tibetan Plateau yaks following short-term exposure to polystyrene microplastics: Analysis of rumen microbiota, host metabolism, antioxidant function and inflammatory responses - Penghu Zhang; Yanbing Zhu; Zhisheng Wang; Peiqiang Yu; Bai Xue; Lizhi Wang; Rui Hu; Huawei Zou; Yahui Jiang; Jianxing Xiao; Cui Tan; Fali Wu; et al. (Journal of Hazardous Materials, 2026)

Metabolic complementarity in LAB-yeast co-fermentation associates with enhanced ester aroma in cream cheese - Beibei Duan; Yueyue Zhou; Siyu Wang; Ling Yan; Yujie Lin; linze Li; Bin Xue; Rui Huang; Yipan Zhang; Yue Cui; Nan Wu; Xiangting Kong; et al. (Food Research International, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

Development of a triplex RT-qPCR assay for rapid and accurate detection of porcine rotavirus, porcine epidemic diarrhea virus, and porcine deltacoronavirus - Yuhan Yang; Xingyu Xiao; Meixuan Ren; Ningning Jiang; Xiaoxu Xie; Xue Zheng; Rui Yin; Shiyu Luan; Jingnan Wang; Peng Li (Veterinary Research Communications, 2026)

Identification of potential mechanisms of quercetin in diabetic peripheral neuropathy through integrated network pharmacology and experimental validation - Zanpeng Chen; Ziyu Li; Xiaowei Xue; Wei Song; Rui Zhang; Chao Wang; Bin Yan; Qing Sun; Qunli Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

CRISPR/Cas9 system inhibits largemouth bass virus infection in vitro and in vivo - Rui-Long He; Mao-sheng He; Xin-Yuan Jiang; Yi-Wang; Hao-Liang; Xiang-Yi Bu; Kun Xu; Fei Ling; Gao-Xue Wang; Hai-Feng Jiang (Aquaculture, 2026)

Grafting on resistant rootstock enhances pepper bacterial spot disease resistance and alters rhizosphere bacterial community - Rui Wang; Yanhui Wang; Yanan Xue; Yuanyuan Wang; Jiayao Liu; Fengzhi Wu; Xingang Zhou (Physiological and Molecular Plant Pathology, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Distribution profiles of 12 isoflavone monomers in Chinese soybeans from saline-alkali and ordinary soils and subsequent supercritical CO₂ extraction optimization - Zixuan Liu; Ziqian Xue; Rui Yang; Xinru Guo; Yutong Zhen; Guiqiao Liu; Chunmei Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2026)

A near-infrared AIEgens-based fluorescent probe with large stokes shift for selective lysine detection: Photophysical properties, chirality transmission, and bioimaging applications - Xin Wang; Wenhui Xue; Penghui Xia; Qian Wang; Shizhen Wang; Yuefeng Zhu; Nuo Fei; Keting Zhu; Yuhan Li; Ruimeng Ye; Yang Liu; Zhixin Dong; et al. (Food Chemistry, 2026)

Upgrading H2/CO2-containing waste gas to single cell protein: Tolerance and response of Cupriavidus necator H16 to hydrogen sulfide - Jie Wang; Rui Li; Manqian Wang; Xuening Wang; Min Xue; Ankun Xu; Kai Luo; Xiaolei Fan; Rongbo Guo; Shanfei Fu (Chemical Engineering Journal, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Soil seed banks, seedlings, and above-ground vegetation co-associate with topography and microhabitat in the forest-grassland ecotone of Loess Plateau, China - Yunyin Xue; Ning Wang; Lu Chen; Guifang Hu; Rui Wang; Jun’e Liu; Liguo Cao; Zhengchao Zhou (Plant and Soil, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Influence of Rate Effects on Fracture-Induced Opening of Interlayer Branch Fractures - Wen-rui Wang; Zong-qing Zhou; Hua-qing Ma; Xue-lin Zheng; Lei Chen; Cheng-lu Gao; Zhi-yuan Liu (Rock Mechanics and Rock Engineering, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

A data-mechanism integrated framework for elucidating the migration and attenuation of light non-aqueous phase liquids in the vadose zone - Zhenkun Xue; Yirong Deng; Rui Zuo; Haijian Lu; Ziyi Wu; Jiawei Liu; Heli Wang; Yuting Zhang; Xiuyu Liang; Jinsheng Wang (Water Research, 2026)

High-performance electrochemical sensor based on an iron phthalocyanine-tetrathiafulvalene polymer for simultaneous detection of catechol and acetaminophen - Chuangyu Wei; Rui Tao; Yang Wang; Meitong Li; Xinyu Yang; Xinrui Niu; Hongyang Man; Xue Cai (Journal of Environmental Chemical Engineering, 2026)

Development of antibacterial and antifouling smart/active food packaging based on phosphorylcholine-modified chitosan for pork freshness monitoring and raspberry preservation - Tiantian Liu; Jiayi Xue; Ruoran Qin; Haoqiang Wang; Rui Zhang; Yingzhu Liu; Longwei Jiang (Food Packaging and Shelf Life, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Construction of a plasmid-based reverse genetics system for the rescue of shrimp infectious covert mortality nodavirus (CMNV) and use in deciphering the role of its B2 protein in regulating its cross-species infectivity - Zhenxin Zhao; Ting Xue; Jinwu Wang; Rui Xiao; Yue Zhang; Meiling Sun; Qingli Zhang; Huarong Guo (Aquaculture, 2026)

Occurrence and dietary risk assessments of polyethoxylated tallow amine in soybeans - Xinru Cui; Zhenjun Liu; Rui Yang; Minjie Li; Xinru Guo; Zixuan Liu; Ziqian Xue; Bei Fan; Zehua Ke; Chunmei Li; Fengzhong Wang (Journal of Hazardous Materials, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Dual-sided Pd functionalization of groove-textured CeO2 hollow microcages boosts room temperature NO2 sensing - Yan Tong; Pengkai Xing; Wenbo Ruan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Muhammad Ikram; Xue Bai; Qin Guo; Keying Shi (Chemical Engineering Journal, 2026)

Hydrothermal-responsive plasmonic aerogel for dynamic 3D hotspot regulation and ultrasensitive SERS detection of dairy products contaminants - Jing-Xiang Wang; Zhi-Gao Xu; Xin-Rui Wang; Yao-Yao Zhang; Ri-Hui Su; Xin-Xin Zhang; Su-Ming Dai; Wei-Wei Zhu; Xue-Cai Tan; Ke-Jing Huang; Jun Yan (Analytica Chimica Acta, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Development of a pectin-based edible active packaging film incorporating curcumin-loaded multilayer nanoparticles to extend the shelf-life of blueberry - Ruoran Qin; Yanyan Wang; Jiayi Xue; Tiantian Liu; Rui Zhang; Haoqiang Wang; Longwei Jiang (Food Hydrocolloids, 2026)

Abandonment duration shapes reuse strategies and benefits of abandoned cropland in China - Yixin Liao; Chenrui Luo; Xue Wang; Jialin Liu; Xiaoqi Huang; Xinliang Xu; Rui Qin; Yuanwei Qin; Luo Liu (Environmental Impact Assessment Review, 2026)

Engineering active oxygen vacancy sites in WO3@COF for efficient photocatalytic hydrogen peroxide production - Yuheng Zhang; Qixin Pan; Chaojie Xing; Jiali Lu; Yunkai Sun; Xiaoqiang Xue; Wei Wang; Che Zhao; Rui Wang (Chemical Engineering Journal, 2026)

Improved corrosion resistance of amorphous-containing dual-structured micro-arc oxidation coatings on (Zr0.5Ti0.35Nb0.15)90Al10 high-entropy alloy - Luqi Chai; Xuehui Yan; Yubo Ma; Lijiao Wang; Xin Li; Chungang Guo; Chi Xu; Jiancheng Du; Xiaoyue Jin; Wenbin Xue; Menglu Zhang; Rui Zuo (Chemical Engineering Journal, 2026)

Defect-rich 3D flower-like SnS2-xSex nanostructures for ultrasensitive NO2 gas sensing at room temperature - Shanshan Cong; Pengkai Xing; Wenbo Ruan; Jiahui Fan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Qin Guo; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

Experimental and numerical analysis of supply air jet in stratum ventilation for cooling - Yong Cheng; Yulong Xie; Rui Wang; Teng Li; Xue Tian (Building and Environment, 2026)

Release Characteristics of Phosphorus in Different Water Layers and its Relationship with Water Nutrient Status of a Typical River in Northern China - Rui Xue; Qiuying Chen; Yuexuan Wang; Qi Wang; Xiuzhong Li (Water, Air, & Soil Pollution, 2026)

Laminarin attenuates neuroinflammation in MPTP-induced Parkinson’s disease mouse model via inhibiting dectin-1/Syk/NF-κB signaling - Rui-Yue Zhao; Mei Zhang; Xiao-Wen Wang; Feng Xue; Yang-Yang Zheng; Wen-Fang Chen (Inflammopharmacology, 2026)

Binasal occlusion modulates cortical functional connectivity and hemodynamics in acquired paralytic esotropia: a fNIRS study - Jie Zhou; Ran Du; Xue Wang; Jun Wu; Fubiao Huang; Rui Fang; Yixiong Liang; Ning Song; Wenbin Wei (Experimental Brain Research, 2026)

Effect of transporter gene polymorphisms and valproate co-medication on the steady-state disposition of lamotrigine and their effect on efficacy in adults with epilepsy - Changsong Wu; Rui He; Jianghuan Zheng; Jing Yang; Yanling Pan; Ruyu Tao; Xue Lan; Jinxingyi Wang (European Journal of Clinical Pharmacology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Rectal nanoparticulate-hydrogel delivering budesonide to reduce enterohepatic drug metabolism and clearance - Rui Xue Zhang; Weijia Lu; Xu Yan; Xudong Deng; Runrun Wan; Zhejun Song; Jiayan Liang; Xue-Ting Wang; Tingting Cao; Yan Chen; Paul K. H. Tam (Drug Delivery and Translational Research, 2026)

Qualitative analysis of chemical constituents and study on the biological activity of Polygonum perfoliatum L - Chaochen Yue; Ya Zhang; Juan Xue; Tian Lu; Lei Li; Yanjie Wang; Rui Zhou; Di Gao; Huifang Chai (Natural Product Research, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Precambrian crustal evolution of the southern margin of the North China Craton: Evidence from the Paleo–Mesoproterozoic sedimentary rock - Shuo Wang; De-Bin Yang; Xiang-Yu Yan; Ke Wu; Jian-Ning Liu; Rui-Qing Xue (Journal of Asian Earth Sciences, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

The enhanced role of glycine in methanesulfonic acid-methylamine-driven nucleation in urban aerosols and coastal industrial regions - Shuqin Wei; Kaiyu Xue; Xiaokai Guo; Wenyuan He; Tianlei Zhang; Rui Wang (Atmospheric Environment, 2026)

Glaucine suppresses IL-16/CD4 to alleviate neuropathic pain via spinal p56lck-NMDA receptor signaling - Xue Li; Rui Wang; Xiaonan Ma; Jin Yang; Shen Zhang; Zimeng Zhang; Han Jiang; Jihua Liu; Boyang Yu; Wenling Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Research on rock mechanics parameter prediction based on the frequency spectrum characteristics of vibration while drilling - Jia-kang Song; Jian-ning Wang; Zhao Ma; Yi-guo Xue; Rui-rui Cai; Fan-meng Kong; Lei Gao (Applied Geophysics, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Effects of borneol on pharmacokinetics and tissue distribution of tetramethylpyrazine in transdermal patch - Lili Cui; Lichun Zha; Jiahua Mei; Rui Xue; Jie Wang; Ziwen Zhang; Yunshu Ma (Drug Delivery and Translational Research, 2026)

Identification of novel B-cell neutralizing epitopes in goose Astrovirus type 2 - Shichao Yuan; Rui Fu; Bangfeng Xu; Wenqing Wang; Huamao Ding; Xue Pan; Chunxiu Yuan; Qinfang Liu; Zhifei Zhang; Qiaoyang Teng; Xiaona Shi; Minghao Yan; et al. (Veterinary Microbiology, 2026)

Controls of surface water-groundwater interaction on the migration and transformation of dissolved organic matter in coastal area - Ying Liang; Xulong Gong; Rui Ma; Changjian Zou; Xue Jiang; Chen Liu; Kaige Ma; Yuan Liu; Yanxin Wang (Journal of Hydrology, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Insights into the effects of different nitrogen sources on microbial metabolic function and biodegradation of bituminous coal - Yundu Yang; Bingjun Liu; Sheng Xue; Junyu Wang; Xiangqing Jiang; Ruifeng Chen; Rui Sun; Keyang Cheng (Fuel, 2026)

Hydration-driven structural engineering via enzymatic glycation: Sustained quercetin release in pullulan-zein coatings for extended walnut preservation - Zi-han Wang; Xue-li Liu; Rui-qi Sun; Bin Qi; Jun-xia Xia; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2026)

Precision in the air: A lightweight, cost-effective, CFD-assisted method for occupant localization and demand-based airflow control in crowded indoor spaces - Zhe Wang; Hao Sun; Mingda Harvey Yang; John Kaiser Calautit; Jianbin Chen; Rui Guan; Zhu Tao; Xue Zheng; Abdullah Dik; Jo Darkwa (Building and Environment, 2026)

A fusing positioning algorithm for small maritime unmanned vehicle - Rui Xue; ShuaiChuang Wang; Jia Wang (Frontiers in Marine Science, 2026)
Introduction The 5th generation (5G) mobile communication and Beidou navigation system (BDS) antennas of offshore small maritime unmanned vehicles (SMUV) are shaken by waves and winds in harsh sea conditions, resulting in poor stability in positioning trajectory tracking and varying degrees of impulse noise in pseudo-range measurements. Methods Therefore, A Kalman filter algorithm combining approximate message passing (AMP) and variational Bayesian (VB) is proposed under a fusion positioning model of 5G and BDS with a high update rate. The AMP algorithm can predict the instantaneous position movement caused by waves, and the VB algorithm smooths the pulse error of trajectory tracking caused by intermittent shielding. Results Experimental results demonstrate that, in 100 positioning epochs, when the impact of waves on SMUV is 20 times, 30 times and 40 times, the root mean square error of the proposed algorithm is 1.19 meter (m), 1.26 m and 1.27 m respectively. Compared with the adaptive variational Bayesian algorithm, the positioning accuracy is improved by 7.75%, 16.4% and 24.4%, which obviously enhances the stability of positioning. Discussion The proposed algorithm can achieve high-precision positioning and tracking, and the performance of the algorithm is better than that of the comparison scheme when the amplitude and frequency of the waves are greater.

PcTCP9-PcANK1 module regulates ester biosynthesis during post-harvest ripening of pear (Pyrus communis L.) - Fengli Zhou; Xue Wang; Wenbing Sang; Guanghuan Xu; Hongjuan Zhang; Caixia Zhang; Rui Zhai; Chengquan Yang; Zhigang Wang; Lingfei Xu (Postharvest Biology and Technology, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Corrigendum to “Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides” [Food Chem. 496(Part 2) (2025) 146787] - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2026)

Efficient bioconversion of corn stover hydrolysates into phenazine-1-carboxylic acid by engineered Pseudomonas chlororaphis for sustainable biopesticide production - Sheng-Jie Yue; Yu-Xuan Li; Kai-Quan Liu; Sheng-Xiao Zhang; Peng Huang; Wei Wang; Xue-Hong Zhang; Xiang-Rui Hao; Lian Jiang; Hong-Bo Hu (Bioresource Technology, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Arbuscular mycorrhizal fungi inoculation enhances 15N uptake by rice via modifying rhizosphere and hyphosphere soil bacterial and fungal community and soil enzyme activity - Pei Chen; Yu Cheng; Rui Chen; Ning Wang; Jianguang Yu; Lihong Xue; Linzhang Yang (Plant and Soil, 2026)

The transition from natural to cultivated monoculture grasslands reshapes nematode taxonomic composition without reducing diversity - Rui Yang; Xue Wei; Jinhao Ma; Xiao Ren; Yuying Wang; Bo Zhu; Pengfei Wu (Applied Soil Ecology, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

A CPP-ESO controller for robust multi-USV formation under complex environments and communication constraints - Xiaomin Wang; Min Xue; Jialin chen; Bin Dou; Rui Yang; Zhendong Sun (Ocean Engineering, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Construction of covalent organic framework electrospun composite nanofiber membranes for the efficient extraction and detection of phenylurea herbicides - Xue-Ying Rui; Bao-Zhu Jia; Peng Wen; Hong Wang; Hong-Tao Lei; Lin Luo; Zhen-Lin Xu (Food Chemistry, 2025)

A high strength, breathable, water resistant chitosan-gelatin composite film modified by tannic acid-synergistic ZIF-8 for blueberry preservation - Huixuan Zhang; Xue Yang; Yingying Zhang; E. Zhao; Haimiao Tian; Keshan Wang; Ning Ji; Yuanyuan Liu; Rui Wang (Food Packaging and Shelf Life, 2025)

Electric field-biochar integrated anammox system for high-efficiency nitrogen and phosphorus removal under elevated nitrogen concentration shock - Rui Hu; Xue Chen; Wanjiang Li; Yule Han; Shiliang Heng; Jiayi Wang; Yijing Gao; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Chemical Engineering Journal, 2025)

A single chitosan-based fluorescent sensor for the discriminant analysis and quantitative detection of bisulfite and oxytetracycline in real samples - Chao Gao; Rui-Xue Li; Xiang Li; Zhenxing Zhong; Jia-Hui Wang; Wei Li (Carbohydrate Polymers, 2025)

Forest greenness stability in response to climate change along forest edge–core gradients - Shaodong Huang; Rui Li; Yujie Li; Siyu Xue; Panfei Fang; Yuying Liang; Jia Wang; Longhuan Wang (Agricultural and Forest Meteorology, 2025)

Groundwater anomaly variation and its response to environment change in an inland river basin, China - Zexia Chen; Wei Liu; Qi Feng; Zhenliang Yin; Meng Zhu; Yuanyuan Xue; Lingge Wang; Chunshuang Fang; Rui Zhu (Journal of Hydrology, 2025)

Qualitative and quantitative detection of Zn2+ in food: design, synthesis and characterization of a near-infrared probe with large Stokes shift - Shizhen Wang; Xin Wang; Wenhui Xue; Yi Huo; Mengyu Chen; Cuibing Bai; Qixiang Song; Chenxu Liu; Lin Zhang; Changqing Qu; Hui Miao; Rui Qiao (Food Chemistry, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Synergistic coupling of Pd@PtRh nanozyme with NiMn2O4/In2S3 Z-scheme heterojunction for ultrasensitive photoelectrochemical sensing of malathion - Rui-Jin Shao; Ke Yin; Lei Zhao; Yadong Xue; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Tuning the disordered microdomains in hard carbon via nitrogen doping for high-performance sodium storage - Zhifei Wang; Zhiyu Xue; Xiaobin Niu; Jiuhui Han; Rui Wu; Dmitry Andreevich Podgorny; Daniel John Blackwood; Chao Li; Jun Song Chen (Chemical Engineering Journal, 2025)

Multifunctional fluorescent sensors N/CDs@Eu-MOFs for rapid detection of childhood obesity and acute myeloid leukemia biomarkers and identification of chiral enantiomers of lysine - Liping Peng; Rui Xue; Henglong Ren; Borong Ren; Mingyue Wang; Xiuli Niu; Hao Guo; Wu Yang (Analytica Chimica Acta, 2025)

Tech-policy integrated validation of spatiotemporal energy-emissions efficiency in public bus systems - Yaxi Xiao; Yangbin Dong; Rui Xue; Zhaocai Meng; Bai Li; Yonghui Hu; Zhanyong Wang (Transportation Research Part D: Transport and Environment, 2025)

Rising mercury consumption from blue foods in China balanced by a shift to lower-mercury choices - Wei Wang; Yumiao Xue; Rui Wang; Pan He; Beibei Liu (Sustainable Production and Consumption, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

In situ electrochemical activation of commercial V2O5 cathodes enabling high-performance aqueous zinc-ion batteries - Changyi Zheng; Wenjian Wang; Feng Liu; Zidong Zhang; Yue Zhang; Fei Han; Rui Zhao; Yao Liu; Linjuan Zhang; Weidong Xue (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Improvement of coronary microcirculation in acute myocardial ischemia rats using a nanoscale carrier SiO2@PEG loaded with Nicorandil - Rui Wang; Yujing Mo; Yingcong Liang; Yuanhui Liu; Zhongchan Sun; Wenting Shang; Ling Xue (Drug Delivery and Translational Research, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Rising mercury consumption from blue foods in China balanced by a shift to lower-mercury choices - Wei Wang; Yumiao Xue; Rui Wang; Pan He; Lei Huang; Beibei Liu (Appetite, 2025)

Construction and application of a quantitative model for calculating LNAPL lateral migration in the capillary zone - Rui Zuo; Ziyi Wu; Jiawei Liu; Shida Zheng; Zuorong Xu; Zhiwen Wang; Zhenkun Xue; Chengzhi Wang (Journal of Hazardous Materials, 2025)

A ratiometric fluorescent sensor based on Eu3 + -β-diketone functionalized covalent organic framework hybrid material-loaded in electrospun polyvinylidene fluoride film for ultra-sensitive and rapid detection of glyphosate - Yingfei Hui; Hao Guo; Rui Xue; Mingyue Wang; Yanyan Ma; Dengke Zhuang; Wu Yang (Journal of Hazardous Materials, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Deciphering the hidden defensive behavior and binding mechanism of anammox process to microcystin from the perspective of granular properties, intracellular metabolism and molecular docking - Xue Chen; Rui Hu; Xintao Wu; Jiandong Wang; Shiliang Heng; Zhaobin Liu; Xueqin Lu; Guangyin Zhen (Journal of Hazardous Materials, 2025)

Phosphogypsum aggregate-based high-permeability pervious concrete preparation: Towards low carbon and environmental friendly - Yike Chen; Xue Liu; Chiqiu Wu; Wei Lv; Kangning Liu; Siyu Wang; Jinyun Zhu; Xiangjun Chen; Rui Yu (Journal of Cleaner Production, 2025)

Catalytic dehydrogenation of propane by electrospinning one-dimensional Zn-Ga2O3-Al2O3 nanofibres under CO2 atmosphere - Rui Chen; Xue Han; Yixuan Yang; Xupeng Yang; Yuqi Wang; Yupeng Zhang; Tiange Huang; Jie Wei; Junjie Ding; Xuyu Wang; Hongbing Ji (Fuel, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Vermicompost maintains topsoil fertility by reducing NH3 volatilization and improving 15N/NO3- retention in a saline-alkali soil - Siping LI; Chong WANG; Huiying HUANG; Jia CAO; Rui XUE; Binglei WANG (Pedosphere, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Multifunctional Janus hydrogel targeting mitochondrial regulation and inflammatory pathways promotes infected burn wound repair - Xiaohui Li; Longbao Feng; Honglin Wu; Hao Yang; Peng Wang; Yongfei Chen; Yuxi Zhou; Jiayuan Zhu; Wei Xue; Rui Guo; Zhicheng Hu (Chemical Engineering Journal, 2025)

BEGV2-UNet: A method for automatic segmentation and calculation of backfat and eye muscle region in pigs - Wenzheng Liu; Tonghai Liu; Jinghan Cai; Zhihan Li; Xue Wang; Rui Zhang; Xiaoyue Seng (Computers and Electronics in Agriculture, 2025)

Listwise ranking predictor for evolutionary neural architecture search - Nan Li; Lianbo Ma; Rui Wang; Shi Cheng; Yanan Sun; Bing Xue; Mengjie Zhang (Swarm and Evolutionary Computation, 2025)

An integrated metabolomics-chemometrics strategy for discovering and characterizing potent anti-tyrosinase activity markers in functional tea Nelumbinis stamen - Yang Liu; Shujing Chen; Xue Meng; Jiake Wen; Rui Wang; Chengda Zhang; Kunze Du; Jin Li; Yanxu Chang (Food Bioscience, 2025)

Dual-recognition strategy sensor based on GO-SELEX aptamer screening for high-specificity identification of fenthion and its major metabolites in vegetables - Lingjun Geng; Haowei Dong; Qingxia Han; Xue Huang; Jingcheng Huang; Haifang Wang; Rui Xu; Jicheng Zhao; Zhouping Wang; Shijia Wu; Ibrahim A. Darwish; Yemin Guo; et al. (Food Bioscience, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Controlled construction of single-atom iron by confined engineering to promote the elimination of harmful organic pollutants - Haijian Wang; Rui Bai; Yicheng Zhang; Zenghui Han; Yingtang Zhou; Xue Zhao (Chemical Engineering Journal, 2025)

Genome-wide characterization of soybean bile acid: sodium symporter genes reveals a positive role of GmBASS2-2 in salt stress response - Xunchao Zhao; Yan Zhang; Yuan Li; Xiuli Rui; Jie Wang; Yuhang Zhan; Yongguang Li; Xue Zhao; Yingpeng Han (Theoretical and Applied Genetics, 2025)

Using open GPS trajectory data to quantify nature-based recreation at a national scale - Pei Wang; Zhicong Zhao; Ruijia Zhu; Hao Wang; Shaochong Xue; Yiwei Liu; Fangyi Wang; Yue Cao; Le Yu; Rui Yang (Resources, Conservation and Recycling, 2025)

Ligand-rich oxygen evolution electrocatalysts reconstructed from metal-organic frameworks for anion-exchange membrane water electrolysis - Shiqi Li; Weiwei Liu; Yi Shi; Tang Wang; Tianyang Liu; Xiang Xue; Rui Li; Man Qiao; Zhen-Yu Wu; Wang Zhang (Science Bulletin, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Research progress and application of carbon sequestration in industrial flue gas by microalgae: A review - Rui Wang; Xue Wang; Tingyu Zhu (Journal of Environmental Sciences, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Heavy-Duty Diesel Trucks on Highways in Beijing-Tianjin-Hebei: Constant Challenge in Pollution Control - Yingying Han; Chang Wang; Yixue Zhu; Rui Wu; Yifeng Xue; Xiang Zhang; Weiwei Wang; Yangyang Cui; Jinxiu Han; Zongbo Shi; Xiuyan Wang; Taosheng Jin (Water, Air, & Soil Pollution, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Glucose-driven synthesis of N-doped porous carbon from sludge for CO2 removal in biomass syngas - Jinpeng Zhai; Zhenjiang Wang; Jia Ouyang; Beichen Xue; Chao Liu; Rui Xiao (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Undrained permanent deformation characteristics of Yellow River silt under one-way cyclic loads - Yuke Wang; Hao Chen; Yujie Xue; Rui Jiang; Xiang Yu; Xiaoying Lin (Marine Georesources & Geotechnology, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

High-throughput screening method for glycolipids based on substrate modification and their efficient biomanufacturing - Yuanyi Li; Zhilin Liu; Yiming Zheng; Ke Sun; Peng Lei; Yian Gu; Yongting Song; Jian Xue; Weidong Cai; Rui Wang; Hong Xu; Liang Sun (Bioresource Technology, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Effects of alternating wet and dry irrigation regimes on rice growth and physiology characteristics in southeast China - Rui Zhou; Haofang Yan; Chuan Zhang; Xingye Zhu; Guoqing Wang; Bin He; Kinda Negessa Disasa; Imran Ali Lakhiar; Run Xue; Yudong Zhou; Biyu Wang; Jun Li; et al. (Paddy and Water Environment, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Chemical characteristics and sources apportionment of volatile organic compounds in the primary urban area of Shijiazhuang, North China Plain - Xiao Zhang; Junfeng Wang; Jiangwei Zhao; Junliang He; Yali Lei; Kai Meng; Rui Wei; Xue Zhang; Miaomiao Zhang; Shuangying Ni; Eleonora Aruffo (Journal of Environmental Sciences, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

2D Laplace-Fourier domain acoustic wave equation modeling with an optimal finite-difference method - Jing-Yu Wang; Na Fan; Xue-Fei Chen; Shou-Rui Zhong; Bo-Yu Li; Dan Li; Gang Zhao (Applied Geophysics, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

Insights into the photoaging behavior of biodegradable and nondegradable microplastics: Spectroscopic and molecular characteristics of dissolved organic matter release - Xiaoyang Wu; Yifan Liu; Yaofeng Jin; Yue Wang; Mengjie Yuan; Kunyu He; Xiaoyan Zhang; Qin Chen; Zhijing Xue; Rui Wang; Xiaoyun Li (Journal of Hazardous Materials, 2025)

The effects of chitosan oligosaccharides on the structure and shelf-life of whole-millet cakes - Yiqing Zhu; Luman Sang; Sameh Sharafeldin; Liangxing Zhao; Rui Chen; Chao Wang; Yong Xue; Qun Shen (Food Chemistry, 2025)

Large-Scale synthesis of crystalline phosphorus nanosheets with superior air-water stability and flame-retardancy ability - Zunbin Duan; Rui Li; He Bian; Yanfang Wang; Xue Zhang; Ziqiang Cheng; Danni Liu; Yang Li; Shuai Zhang; Guangbo Qu; Paul K. Chu; Jiahong Wang (Chemical Engineering Journal, 2025)

Transcriptome Analysis Reveals the lncRNA-mRNA Co-expression Network Regulating the Aestivation of Sea Cucumber - Xiaomei Chen; Wentao Han; Rui Yang; Xuan Zhu; Shengwen Li; Yangfan Wang; Xue Sun; Yuli Li; Lisui Bao; Lingling Zhang; Shi Wang; Jing Wang (Marine Biotechnology, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

KOH-modified biochar enhances nitrogen metabolism of the chloroquine phosphate-disturbed anammox: Physical binding, EPS modulation and versatile metabolic hierarchy - Rui Hu; Xue Chen; Yule Han; Wanjiang Li; Shuting Zhang; Zhaobin Liu; Jiandong Wang; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2025)

Atomically dispersed iron & iron clusters synergistically accelerate electrocatalytic ammonia synthesis - Haoran Zhang; Yuelong Liu; Sanshuang Gao; Haijian Wang; Rui Bai; Yan Zhao; Yingtang Zhou; Guangzhi Hu; Xue Zhao (Chemical Engineering Journal, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Microalgae biofilm barrier to assist the simultaneous nitrogen and phosphorus removal in anammox: Molecular mechanism on sludge granulation and microbial metabolism - Xue Chen; Rui Hu; Mengting Xia; Shiliang Heng; Jiandong Wang; Zhaobin Liu; Jiahua Tian; Xueqin Lu; Guangyin Zhen (Chemical Engineering Journal, 2024)

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

Ferritinophagy is involved in hexavalent chromium-induced ferroptosis in Sertoli cells - Ruijian Zhuge; Le Zhang; Qian Xue; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Chunyang Meng; Rifeng Lu; Fei Yin; Li Guo (Toxicology and Applied Pharmacology, 2024)

Hexavalent chromium reduces testosterone levels by impairing lipophagy and disrupting lipid metabolism homeostasis: Based on a metabolomic analysis - Qian Xue; Le Zhang; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Shidi Gao; Xin Fang; Chunyang Meng; Rifeng Lu; Li Guo (Toxicology, 2024)

Quantitative expression of LNAPL pollutant concentrations in capillary zone by coupling multiple environmental factors based on random forest algorithm - Kexue Han; Rui Zuo; Donghui Xu; Xiao Zhao; Jian Shi; Zhenkun Xue; Yunxiang Xu; Ziyi Wu; Jinsheng Wang (Journal of Hazardous Materials, 2024)

Simultaneous removal of ammonia nitrogen, sulfamethoxazole, and antibiotic resistance genes in self-corrosion microelectrolysis-enhanced counter-diffusion biofilm system - Ying Xue; Yufei Cheng; Qingru Wang; Rui Zhao; Xiaohang Han; Junqin Zhu; Langming Bai; Guibai Li; Han Zhang; Heng Liang (Bioresource Technology, 2024)

Vermicompost enhances the salt tolerance of maize by reshaping the rhizosphere microenvironment - Mengli Liu; Jia Cao; Chong Wang; Binglei Wang; Rui Xue (Applied Soil Ecology, 2024)

Antimicrobial blue light inactivation of Pseudomonas aeruginosa: Unraveling the multifaceted impact of wavelength, growth stage, and medium composition - Yucheng Wang; Xue Li; Hongtong Chen; Xinyi Yang; Lei Guo; Rui Ju; Tianhong Dai; Guoqing Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Effect of anaerobic duration on nitrogen and phosphorus removal and carbon source utilization in integrated denitrifying phosphorus removal and partial denitrification coupled with anammox system - Yunlong Su; Xiyao Li; Jiao Wang; Rui Du; Xiaofei Xue; Yanwei Shi; Yongzhen Peng (Journal of Cleaner Production, 2024)

Ultrasound-responsive ZnS:Ag QDs loaded TiO2 biointerfaces: In situ sonodynamic antimicrobial therapy for biomedical implants - Lei Ji; Yun Xue; Dong Wang; Yu Fan; You Zhou; Chuanan Shen; Rui Shi; Jiatao Zhang (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Earthworms and Arbuscular Mycorrhizal Fungi Alleviated Salt Stress in Maize Seedlings by Regulating the Root Endodermis Diffusion Barrier - Binglei wang; Chong Wang; Lei Zhao; Xuelian Liu; Rui Xue; Jia Cao; Siping Li; Mengyao Guo; Huiying Huang (Journal of Plant Growth Regulation, 2024)

Robust control algorithm designed for robotic legs of lunar-based equipment: Modeling and experiment - Zheng-Han Chen; Zhao-Dong Xu; Rui-Heng Wang; Hong-Fang Lu; Deng-Yun Yu; Jian-Zhong Yang; Xue-Liang Zhao; Zhong-Wei Hu; Sheng-Chao Zhen (Advances in Space Research, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

Mutations in wheat TaAPA2 gene result in pleiotropic effects on plant architecture - Shengsheng Bai; Guiping Wang; Rui Song; Yanna Liu; Lei Hua; Jinwei Yang; Lijun Zhang; Shams ur Rehman; Xiaohua Hao; Lifeng Hou; Chaozhong Zhang; Hongna Li; et al. (Science China Life Sciences, 2024)

Correction to: Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Sandwich-structured continuous ZIF-8/Ti3C2 MXene/ZIF-8 for efficient sterilization: Enhanced photocatalytic activity, photothermal effect, and environmental safety - Furong Xiong; Huilin Hu; Xiang Xue; Minqi Wu; Jiajie Zhou; Wang Zhang; Rui Li (Water Research, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Chemical adsorption reaction process and mechanism of n-hexadecane pollutant–water–medium particles in soil - Kexue Han; Rui Zuo; Guanlan Wu; Donghui Xu; Xiao Zhao; Jian Shi; Zhenkun Xue; Yunxiang Xu; Ziyi Wu; Jinsheng Wang (Journal of Hydrology, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Cement-based external wall insulation material with thermal performance improvement by partial substitution of calcium silicate - Wen Rui Ren; Cheng Hai Wang; Chang Bao Han; Dong Han; Jia Yu Zheng; Ya Nan Cui; Xue Mei Song; Quan Jiang; Hui Yan (Energy and Buildings, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Decoding the influence of low temperature on biofilm development: The hidden roles of c-di-GMP - Yu-Ting Lin; Yong-Chao Wang; Yi-Mei Xue; Zhen Tong; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden; Can Wang (Science of The Total Environment, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Electrochemically assisted preparation of graphitic carbon nitride nanosheet membranes for efficient water purification - Yisa Zhou; Ya Zhang; Jian Xue; Rui Wang; Jiale Dong; Zongjie Yin; Chen Guo; Haihui Wang (Chemical Engineering Journal, 2024)

Artemisia argyi H. Lév. & Vaniot: a comprehensive review on traditional uses, phytochemistry, and pharmacological activities - Wen-Jun Wei; Tao Guo; Gui-Min Xue; Rui Ma; Yuefei Wang; Zhe-Sheng Chen (Phytochemistry Reviews, 2024)

Cytotoxicity sesquiterpenoids from the leaves of Datura stramonium L. - Juan Pan; Yan Liu; Ao-Fei Wang; Jia-Tong Wu; Rui Yang; Wei Guan; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Spatial distribution characteristics and degradation mechanism of microorganisms in n-hexadecane contaminated vadose zone - Kexue Han; Rui Zuo; Xiaoyuan Cao; Donghui Xu; Xiao Zhao; Jian Shi; Zhenkun Xue; Yunxiang Xu; Ziyi Wu; Jinsheng Wang (Science of The Total Environment, 2024)

Impact of remaining roots on soil nematode communities in an aboveground plant functional group removal experiment - Yong Zheng; Ligai Huang; Xue Jiang; Rui Guo; Wenjie Wan; Luping Ye; Tibor A. Drost; Xianhui Zhou; Hui Guo; Juan Zuo; Peng Wang (Plant and Soil, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Framework of land use planning for an energy producing city of Northwest China based on water-energy-food nexus - Zhou Fang; Shi Xue; Changgao Cheng; Qin Zhou; Maroof Ali; Rui Xu; Jinxue Xu; Tonghui Ding; Jie Wang; Zhongde Huang; Xiping Sun; Yang Bai (Journal of Cleaner Production, 2024)

Two-dimensional peak-valley alternating self-supporting electrode accelerating nitrate electrocatalytic reduction: Ammonia synthesis and wastewater treatment - Yuelong Liu; Haoran Zhang; Rui Bai; Haijian Wang; Yan Zhao; Yingtang Zhou; Xue Zhao (Chemical Engineering Journal, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Critical fractions in reclaimed water responsible for membrane fouling: Isolation, fouling characteristics, quantitative and qualitative variations in practical application - Yuan Bai; Rui-Ning Wang; Yin-Hu Wu; Song Xue; Zhuo Chen; Hong-Ying Hu (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Effects of environmental and nutritional labels on the dietary choices of consumers: Evidence from China - Xue Sun; Rui Wang; Pan He; Beibei Liu (Environmental Impact Assessment Review, 2024)

Chameleon-inspired supramolecular materials based on cucurbit[7]uril and viologens exhibiting full-color tunable photochromic behavior - Dong-Xue Xia; Xin Wang; Wen-Qi Sun; Rui-Lian Lin; Jing-Xin Liu; Ying-Wei Yang (Chemical Engineering Journal, 2024)

Life cycle analysis of common landfill final cover systems focusing on carbon neutrality - Charles Wang Wai Ng; Hongqi Chen; Haowen Guo; Rui Chen; Qiang Xue (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Preparation of conjugated linoleic acid-rich oleogel emulsions by dynamic high-pressure microfluidization technology - Dianyu Yu; Na Li; Rui Wang; Wenlin Xue; Donghua Wang; Walid Elfalleh; Lanxia Qin; Fengying Xie (Journal of Food Engineering, 2024)

TRPML1 contributes to antimony-induced nephrotoxicity by initiating ferroptosis via chaperone-mediated autophagy - Lei Liu; Chao Luo; Dongnan Zheng; Xuehai Wang; Rui Wang; Wenjie Ding; Zhaoping Shen; Peng Xue; Shali Yu; Yifei Liu; Xinyuan Zhao (Food and Chemical Toxicology, 2024)

Effect of ambient high-temperature on real driving emission tests of a light-duty gasoline vehicle - Rui Wang; Li Zhang; Jingde Peng; Jinlin Han; Baocheng Du; Baoli Gong; Haoyang Xue; Dajiang Tuo; Qing Zhang (Atmospheric Pollution Research, 2024)

Effects of drought stress on seed germination and early seeding growth in Ferula ferulaeoides (Steud.) Korov. - Ying Ma; Kai Liao; Yun Zhu; Xin Lu; Kuan Wang; Xue Rui Zhang (Brazilian Journal of Botany, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Comparison of the ozone formation mechanisms and VOCs apportionment in different ozone pollution episodes in urban Beijing in 2019 and 2020: Insights for ozone pollution control strategies - Yunfeng Li; Zhenhai Wu; Yuanyuan Ji; Tianshu Chen; Hong Li; Rui Gao; Likun Xue; Yafei Wang; Yuxi Zhao; Xin Yang (Science of The Total Environment, 2024)

How does global value chain embeddedness affect environmental pollution? Evidence from Chinese enterprises - Siqi Wu; Tianlei Wei; Yue Qu; Rui Xue; Huiqing Wang; Yuli Shan (Journal of Cleaner Production, 2024)

A metabolomics discrimination-based strategy for screening the antithrombin active markers of perilla seeds: A natural oil crop - Suyi Liu; Xingyue Jin; Rui Wang; Xue Meng; Kunze Du; Jin Li; Xiumei Gao; Yanxu Chang (Food Chemistry, 2024)

Identification of large yellow croakers (Larimichthys crocea) scavenger receptor genes: Involvement in immune response to Pseudomonas plecoglossicida infection and hypoxia-exposure experiments - Xuanyang Sun; Ning Bao; Chen Rui; Yadong Xue; Qian Fang; Tianyu Zheng; Ziyang Lin; Xiumei Liu; Xubo Wang (Fish & Shellfish Immunology, 2024)

Urea-boosted gas-exfoliation synthesis of lignin-derived porous carbon for zinc ion hybrid supercapacitors - Beichen Xue; Chaozhen Liu; Xiaofeng Wang; Yi Feng; Jiahuan Xu; Feng Gong; Rui Xiao (Chemical Engineering Journal, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Leaf spot on cucumber caused by Stemphylium vesicarium newly reported in China - Xiaoyan Yu; Rui Han; Weiqian Zhang; Zhihua Li; Xue Zhang; Xiangjing Wang; Wensheng Xiang; Junwei Zhao (Crop Protection, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Significant methane ebullition from large shallow eutrophic lakes of the semi-arid region of northern China - Linxiang Zhang; Xiangwei Li; Ruihong Yu; Yue Geng; Liangqi Sun; Heyang Sun; Yuan Li; Zhonghua Zhang; Xiangyu Zhang; Xue Lei; Rui Wang; Changwei Lu; et al. (Journal of Environmental Management, 2023)

Successful start-up of a novel integrated denitrifying phosphorus removal and partial denitrification coupled with anammox process for simultaneous nitrogen and phosphorus removal with fully ordinary suspended sludge - Yunlong Su; Rui Du; Jiao Wang; Junfei Qiao; Xiyao Li; Xiaofei Xue; Zhiqi Cao; Yongzhen Peng (Chemical Engineering Journal, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Highly sensitive detection of Salmonella based on dual-functional HCR-mediated multivalent aptamer and amplification-free CRISPR/Cas12a system - Zhaohui Qiao; Liangliang Xue; Mengni Sun; Min Zhang; Min Chen; Xia Xu; Wenge Yang; Rui Wang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Engineering a Pseudomonas putida as living quorum quencher for biofilm formation inhibition, benzenes degradation, and environmental risk evaluation - Yi-Mei Xue; Yong-Chao Wang; Yu-Ting Lin; Guan-Yu Jiang; Rui Chen; Ruo-Lin Qin; Xiao-Qiang Jia; Can Wang (Water Research, 2023)

The adverse impact of corporate ESG controversies on sustainable investment - Rui Xue; Hongqi Wang; Yuhao Yang; Martina K. Linnenluecke; Kaifang Jin; Cynthia Weiyi Cai (Journal of Cleaner Production, 2023)

Constituents of the fruits of Rubus chingii Hu and their neuroprotective effects on human neuroblastoma SH-SY5Y cells - Jingyi Wang; Xue Zhang; Jundong Yu; Jun Du; Xiaohong Wu; Liang Chen; Rui Wang; Yingchun Wu; Yiming Li (Food Research International, 2023)

Approach to characterize rock fracture surface: Insight from roughness and fractal dimension - Bangxiang Li; Weimeng Zhang; Yiguo Xue; Zhiqiang Li; Fanmeng Kong; Rui Kong; Gang Wang (Engineering Geology, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

ZIF-derived Fe,Co coordinated N/O-codoped three-dimensional tungsten–carbon matrix for the performance-enhanced zinc-air flow battery and water splitting - Jinling Xue; Zhipeng Liu; Yibin Fan; Rui Wang; Yinshi Li (Chemical Engineering Journal, 2023)

Pilot-scale demonstration of self-enrichment of anammox bacteria in a two-stage nitrification-denitrification suspended sludge system treating municipal wastewater under extremely low nitrogen loading rate - Yunlong Su; Rui Du; Jiao Wang; Xiyao Li; Qiong Zhang; Xiaofei Xue; Yongzhen Peng (Bioresource Technology, 2023)

Multiphase wavefield inversion methodology for seismic analysis of soil-structure interaction systems - Gang Li; Yaohui Xue; Rui Wang; Han Zhang; Zhiqian Dong; Dinghao Yu (Soil Dynamics and Earthquake Engineering, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Acetylcholine (ACh) enhances Cd tolerance through transporting ACh in vesicles and modifying Cd absorption in duckweed (Lemna turionifera 5511) - Lin Yang; Xu Ma; Yuhan Guo; Yuman He; Yunwen Yang; Wenqiao Wang; Ziyi Xu; Zhaojiang Zuo; Ying Xue; Rui Yang; Bing Han; Jinsheng Sun (Environmental Pollution, 2023)

Emission accounting and drivers in Central Asian countries - Congyu Zhao; Binyuan Liu; Jieyu Wang; Rui Xue; Yuli Shan; Can Cui; Xiucheng Dong; Kangyin Dong (Environmental Science and Pollution Research, 2023)
Emerging countries are at the frontier of climate change actions, and carbon emissions accounting provides a quantifiable measure of the environmental impact of economic activities, which allows for comparisons of emissions across different entities. However, currently there is no study covering detailed emissions inventories for emerging countries in Central Asian. This paper compiles detailed and accurate carbon emissions inventories in several Central Asian countries (i.e., Kazakhstan, Kyrgyzstan, Pakistan, Palestine, Tajikistan, and Uzbekistan) during the period 2010–2020. Using the IPCC administrative territorial approach, we for the first time compile their emissions inventories in 47 economic sectors and five energy categories. Moreover, we also investigate decoupling status based on Tapio decoupling model and examine emissions driving factors based on the index decomposition analysis method. The primary results illustrate that carbon emissions in Central Asian countries are increasing with huge differences. Decoupling results highlight that most of the sample countries still need more effort to decouple the economy and emissions except that Pakistan achieves an ideal strong decoupling state. The results of the decomposition indicate that the economy and population both raise emissions, while energy intensity and carbon intensity are negative drivers in some countries. We propose practical policy implications for decarbonization and energy transition roadmap in Central Asian countries.

Insecticide resistance: Status and potential mechanisms in Aedes aegypti - Yifan Wang; Xin Wang; Dylan J. Brown; Mengru An; Rui-De Xue; Nannan Liu (Pesticide Biochemistry and Physiology, 2023)

Tailoring zincophilicity via amorphous Se-rich selenides coating for stable Zn anode - Guoquan Jiang; Rui Xue; Linxin He; Junchao Zhu; Nan Qiu; Yuan Wang (Chemical Engineering Journal, 2023)

A surface-induced coating strategy for constructing hydrophobic zeolite composite to enhance the toluene adsorption in humid environment - Shuangchun Lu; Wenjuan Xue; Hao Wang; Qingling Liu; Rui Han; Donghai Mei (Chemical Engineering Journal, 2023)

Agricultural intensification weakens soil multifunctionality by reducing fungal diversity - Rui Xue; Chong Wang; Lei Zhao; Jia Cao; Mengli Liu; Dong Zhang (Applied Soil Ecology, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

A method establishment and application for biofilm quorum quenching activity assay - Zhen Tong; Yong-Chao Wang; Guan-Yu Jiang; Xu-Rui Hu; Yi-Mei Xue; Can Wang (Chemosphere, 2023)

Formation and preservation of ultra-deep liquid petroleum in the Ordovician sedimentary succession in Tarim Basin during the neotectonic phase - Feng Li; Xiuxiang Lü; Guangyou Zhu; Jianfa Chen; Rui Wang; Zhenghui Wu; Tao He; Nan Xue (Journal of Asian Earth Sciences, 2023)

Constructing dendrite suppressing mixed sulfide solid electrolyte for high-rate lithium metal batteries - Zeyu Ge; Nanshan Chen; Rui Wang; Rui Ma; Bo Fan; David Le coq; Xianghua Zhang; Hongli Ma; Bai Xue (Chemical Engineering Journal, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Enhanced nitrate reduction by metal deposited g-C3N4/rGO/TiO2 Z-schematic photocatalysts: Performance and mechanism comparison of Pd-Cu and Ag - Houfen Li; Shuai Xue; Fang Cao; Cong Gao; Qian Wei; Rui Li; Aijuan Zhou; Sufang Wang; Xiuping Yue (Chemosphere, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Physicochemical Characterization of Three Active Pharmaceutical Ingredients for Compound Glycyrrhizin Solid Formulation and Compatibility Analysis via Thermal and Non-thermal Techniques - Xiang-yun Xie; Zhan-ying Chang; Chun-li Chen; Liang Zhang; Mei Wang; Cheng Tang; Hong-rui Xue; Xiao-li Gao (Journal of Pharmaceutical Innovation, 2023)

Short- and medium-chain chlorinated paraffins in urban road dust of Shanghai, China: concentrations, source apportionment and human exposure assessment - Xue-Tong Wang; Cheng-Lin Wang; Ying Zhou; Guo-Fa Ren; Rui Fu; Jing An (Environmental Geochemistry and Health, 2023)

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

Identification of the chemical constituents in Cullen corylifolium ethanolic extract by LC-MS/MS and GC-MS - Hongzheng Wang; Keyu Chen; Rui Xue; Chimengul Turghun; Bo Han (Natural Product Research, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Influence of Soil Plug on the Seismic Response of Bucket Foundations in Liquefiable Seabed - Xue-Qian Qu; Rui Wang; Jian-Min Zhang; Ben He (Journal of Marine Science and Engineering, 2023)
The suction installation process for bucket foundations for offshore wind turbines (OWTs) can cause the formation of soil plug within the bucket, which can affect the seismic performance of the OWT. Therefore, it is important to evaluate the influence of soil plug on the seismic performance of OWT on bucket foundations. In this study, a comprehensive set of high-fidelity solid–fluid coupled dynamic numerical simulations are conducted to analyze the seismic response of bucket foundations with a focus on the influence of soil plug and its potential mitigation. The influence of different bucket models, seabed soil densities, seabed inclination and reinforcement types, as well as soil plug removal techniques, are investigated. The results clearly show that the existence of soil plug has a significant unfavorable influence on the seismic performance of OWT on bucket foundations, especially for wide bucket foundations in mildly inclined seabeds, and should be considered in seismic design. Reinforcement methods, such as the application of an inner compartments, outer wings and inner pile, can improve the seismic performance of OWT on bucket foundations, with the application of an inner compartment being the most effective. Soil plug removal can alleviate the negative influence of soil plug, and should be adopted when possible.

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Selenium alleviates endoplasmic reticulum calcium depletion-induced endoplasmic reticulum stress and apoptosis in chicken myocardium after mercuric chloride exposure - Pei-Chao Gao; An-Qi Wang; Xue-Wei Chen; Han Cui; Yue Li; Rui-Feng Fan (Environmental Science and Pollution Research, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Modeling on cryogenic heat exchangers considering variable properties, axial heat conduction and viscous heating - Xue-shuo Shang; Zhuo Miao; Huai-qing Cao; Rui Wang; Wei Shao; Zheng Cui (International Journal of Refrigeration, 2023)

MicroRNA-588 regulates the invasive, migratory and vasculogenic mimicry-forming abilities of hypoxic glioma cells by targeting ROBO1 - Rui Yu; Rongrong Zhao; Xiaopeng Sun; Zongpu Zhang; Shaobo Wang; Xiao Gao; Zhongzheng Sun; Hao Xue; Gang Li (Molecular Biology Reports, 2023)
Background The microenvironment of hypoxia is an important factor contributing to the development of glioblastoma (GBM). MicroRNA-588 and its potential target Roundabout-directed receptor 1 (ROBO1) have been reported to promote tumor invasion and proliferation in diseases such as gastric, pancreatic and hepatocellular carcinoma, while their function in GBM and response to hypoxic states remain elusive. Methods A microarray was leveraged to identify differentially expressed microRNAs in U251 glioma cells cultured under normoxic and hypoxic conditions. The expression of miR-588 was assessed using quantitative real-time PCR (qRT‒PCR). Gain- and loss-of-function studies were used to evaluate the role of miR-588 under hypoxic and normoxic conditions. Cell invasion, migration, proliferation, and vasculogenic mimicry (VM) formation experiments were performed. The relationship between miR-588 and ROBO1 was confirmed using western blot and luciferase reporter assays. Intracranial xenograft tumor mouse models were used to study the function of miR-588 in vivo. Results The expression of miR-588 was significantly upregulated in hypoxic glioma cells relative to normoxic glioma cells. miR-588 inhibited the invasive, migratory and VM-forming abilities of glioma cells in vitro and in vivo. Mechanistically, roundabout guidance receptor 1 (ROBO1) is a direct, functionally relevant target of miR-588 in glioma. ROBO1 knockdown suppressed the expression of matrix metallopeptidase 2 (MMP2) and matrix metallopeptidase 9 (MMP9), thereby inhibiting the invasive, migratory and VM-forming abilities of glioma. Conclusions MiR-588 regulated the behaviors of hypoxic glioma cells by targeting ROBO1. miR-588 can be used as a prognostic marker for glioma and has potential implications in glioma gene therapy.

Effects of earthworm (Eisenia fetida) and arbuscular mycorrhizal fungi improving plant hormones and antioxidant enzymes under simulated acid rain stress - Wang Binglei; Wang Chong; Liu Xuelian; Xue Rui; Liu Mengli; Xu Guangxia; Li Zhiyi (Applied Soil Ecology, 2023)

Evaluation of the pathogenesis of non-typical strain with α-hemolysin, Vibrio parahaemolyticus 353, isolated from Chinese seafood through comparative genome and transcriptome analysis - Fei Zha; Rui Pang; Shixuan Huang; Jumei Zhang; Juan Wang; Moutong Chen; Liang Xue; Qinghua Ye; Shi Wu; Meiyan Yang; Qihui Gu; Yu Ding; et al. (Marine Pollution Bulletin, 2023)

Seasonal variation and ecological risk assessment of Pharmaceuticals and Personal Care Products (PPCPs) in a typical semi-enclosed bay — The Bohai Bay in northern China - Kun Lin; Rui Wang; Tongzhu Han; Liju Tan; Xue Yang; Mengmeng Wan; Yanshan Chen; Ting Zhao; Shan Jiang; Jiangtao Wang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Rapid enrichment of anammox bacteria and transformation to partial denitrification/anammox with nitrification/denitrification sludge - Yunlong Su; Yongzhen Peng; Jiao Wang; Qiong Zhang; Xiyao Li; Shuying Wang; Xiaofei Xue; Rui Du (Science of The Total Environment, 2023)

Correlation analysis and modeling of human thermal sensation with multiple physiological markers: An experimental study - Kangji Li; Rui Yu; Yufei Liu; Junqiang Wang; Wenping Xue (Energy and Buildings, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Clinical Decision on Disorders of Consciousness After Acquired Brain Injury: Stepping Forward - Rui-Zhe Zheng; Zeng-Xin Qi; Zhe Wang; Ze-Yu Xu; Xue-Hai Wu; Ying Mao (Neuroscience Bulletin, 2023)

Tectonic framework of Eastern Tianshan in the Early Carboniferous: constraints from alkalic intrusive rocks - Yi-Hao Liu; Chun-Ji Xue; Yun Zhao; Rui Wang; Liang Yu (International Journal of Earth Sciences, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

U-net Models Based on Computed Tomography Perfusion Predict Tissue Outcome in Patients with Different Reperfusion Patterns - Yaode He; Zhongyu Luo; Ying Zhou; Rui Xue; Jiaping Li; Haitao Hu; Shenqiang Yan; Zhicai Chen; Jianan Wang; Min Lou (Translational Stroke Research, 2022)

The protective effects of procyanidin supplementation on PM2.5-induced acute cardiac injury in rats - Bowen Yin; Xiao Zhang; Jingyi Ren; Fengge Chen; Jufeng Liang; Hanning Zhang; Huanting Pei; Zhaohui Hu; Yan Wang; Wei Xue; Xinyue Yu; Rui Zhang; et al. (Environmental Science and Pollution Research, 2022)

Stability of Bacterial Network Enhances Nutrient Content in Apple Trees - Rui Xue; Chong Wang; Dong Zhang (Journal of Soil Science and Plant Nutrition, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Effects of different energy diets on DNA methylation and mRNA expression in follicle stimulating hormone receptor gene promoter region of Duolang sheep during estrus - Bo Liu; Hongjian Li; Weikun Tao; Fei Huang; Xue Rui; Jie Wang; Peng Niu; Di Fang; Qinghua Gao (Molecular Biology Reports, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Correction to: A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2022)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Summery Intra-Tidal Variations of Suspended Sediment Transportation – Topographical Response and Dynamical Mechanism in the Aoshan Bay and Surrounding Area, Shandong Peninsula - Yan Wang; Yanguang Dou; Liang Zou; Fei Gao; Dapeng Su; Rui Hu; Baojing Yue; Biying Xue (Journal of Ocean University of China, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Mild encephalitis/encephalopathy with a reversible splenial lesion associated with respiratory syncytial virus infection in infants - Xue-Lin Li; Jinming Han; Zhong-Rui Yan; Bing-Wei Zhang; Hai-Yang Wang (Journal of NeuroVirology, 2021)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Application of DNA barcoding and metabarcoding for species identification in salmon products - Nan Wang; Ran-Ran Xing; Meng-Yue Zhou; Rui-Xue Sun; Jian-Xun Han; Jiu-Kai Zhang; Wen-Jie Zheng; Ying Chen (Food Additives & Contaminants: Part A, 2021)

A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Ca2+/Calmodulin-NOS/NO-TNFs Pathway Hallmarks the Inflammation Response of Oyster During Aerial Exposure - Hao Chen; Lusheng Xin; Lin Wang; Huan Zhang; Rui Liu; Hao Wang; Xue Qiao; Lingling Wang; Linsheng Song (Frontiers in Marine Science, 2021)
Aerial exposure (emersion) due to the periodical ebb and flow of tides is a major stressor for intertidal organisms and a key environmental factor in shaping their local communities. Oysters are among the most emersion-tolerant mollusk species and can survive for several days under aerial exposure. Noticeably, overwhelming inflammation responses could occur during the emersion stress. However, mechanisms beneath the activation and modulation of emersion-induced inflammation response have remained largely unknown. Ca 2+ is an important intracellular second messenger that plays indispensable roles in inflammation response by cooperation with calmodulin (CaM) genes. Here, we showed that intracellular Ca 2+ accumulates rapidly in oyster hemocytes during emersion stress along with the changes in the protein levels of three CaM genes, which function as intracellular sensors of Ca 2+ . As downstream effector of Ca 2+ /CaM complex, nitric oxide synthase (NOS) activity in hemocytes was enhanced during the emersion stress, facilitating a greater production of nitrite oxide (NO). Augmentation of NO concentration was associated with the increased mRNA expression levels of two oyster cytokines (CgTNFs) during aerial exposure. The robust accumulation of cytokines and severe injury of tissues in oysters have been regarded as potential cause and marker of their death in prolonged emersion stress. Here, both the expression levels of CgTNFs and the tissue injuries of oysters were attenuated when Ca 2+ /CaM complex or NOS activity were repressed in vivo during the emersion stress. These findings indicate that Ca 2+ /CaM-NOS/NO-CgTNFs pathway is critically involved in the emersion-induced inflammation response in oysters and plays a role in the resistance against long-term aerial exposure.

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Complete genome sequence of a novel mycovirus isolated from the phytopathogenic fungus Corynespora cassiicola in China - Yanfen Wang; Hang Zhao; Caiying Xue; Chao Xu; Yuehua Geng; Rui Zang; Yuxia Guo; Haiyan Wu; Meng Zhang (Archives of Virology, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Separating and imaging diffractions in dip domain on the basis of slope analysis - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2020)

Competitive interactions between two allelopathic algal species: Heterosigma akashiwo and Phaeodactylum tricornutum - Rui Wang; Qiaona Xue; Jiangtao Wang; Liju Tan (Marine Biology Research, 2020)

Advances in research of the mid-deep South China Sea circulation - Dongxiao Wang; Qiang Wang; Shuqun Cai; Xiaodong Shang; Shiqiu Peng; Yeqiang Shu; Jingen Xiao; Xiaohui Xie; Zhiwei Zhang; Zhiqiang Liu; Jian Lan; Dake Chen; et al. (Science China Earth Sciences, 2019)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Development of a colloidal gold-based immunochromatographic strip for rapid detection of Rice stripe virus - De-qing Huang; Rui Chen; Ya-qin Wang; Jian Hong; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2019)

Pine needles as biomonitors of polybrominated diphenyl ethers and emerging flame retardants in the atmosphere of Shanghai, China: occurrence, spatial distributions, and possible sources - Hao-Hao Jia; Xue-Tong Wang; Hang-Xin Cheng; Ying Zhou; Rui Fu (Environmental Science and Pollution Research, 2019)

Initial analysis of the BDS satellite autonomous integrity monitoring capability - Yueling Cao; Xiaogong Hu; Jinping Chen; Lang Bian; Wei Wang; Rui Li; Xue Wang; Yongnan Rao; Xin Meng; Bin Wu (GPS Solutions, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Acupuncture Prevents the Impairment of Hippocampal LTP Through β1-AR in Vascular Dementia Rats - Ling-Yong Xiao; Xue-Rui Wang; Jing-Wen Yang; Yang Ye; Wen Zhu; Yan Cao; Si-Ming Ma; Cun-Zhi Liu (Molecular Neurobiology, 2018)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Impact of Land Use Change on Hydrologic Processes in a Large Plain Irrigation District - Xiao-Bo Luan; Pu-Te Wu; Shi-Kun Sun; Xiao-Lei Li; Yu-Bao Wang; Xue-Rui Gao (Water Resources Management, 2018)

Low-level concentrations of aminoglycoside antibiotics induce the aggregation of cyanobacteria - Lin-Rui Tan; Peng-Fei Xia; Raymond J. Zeng; Qian Li; Xue-Fei Sun; Shu-Guang Wang (Environmental Science and Pollution Research, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Comparative growth increments of gladius surface and cross-sections to estimate Sthenoteuthis oualaniensis age - Xue Feng Wang; Bi Lin Liu; Jian Hua Li; Rui Jiang; Jing Yuan Lin; Teng Li (Marine Biology, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Upper bound estimation of positioning error for ground-based augmentation system - Rui Xue; Zhipeng Wang; Yanbo Zhu (GPS Solutions, 2017)

Spatiotemporal Variability of Contaminants in Lake Water and Their Risks to Human Health: A Case Study of the Shahu Lake Tourist Area, Northwest China - Peiyue Li; Wei Feng; Chenyang Xue; Rui Tian; Siting Wang (Exposure and Health, 2017)

Diffraction separation by plane-wave prediction filtering - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China - Yi-Wei Peng; Xue-Xiang Gu; Peng-Rui Lv; Yong-Mei Zhang; Wen-Bin Cheng; Xin-Li Wang (International Geology Review, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Molecular cloning and expression analysis of two FAD2 genes from chia (Salvia hispanica) - Yufei Xue; Nengwen Yin; Baojun Chen; Feifei Liao; Aung Naing Win; Jiayi Jiang; Rui Wang; Xiaoyun Jin; Na Lin; Yourong Chai (Acta Physiologiae Plantarum, 2017)

Cloning and expression of Perilla frutescens FAD2 gene and polymorphism analysis among cultivars - Yufei Xue; Xingcui Zhang; Rui Wang; Baojun Chen; Jiayi Jiang; Aung Naing Win; Yourong Chai (Acta Physiologiae Plantarum, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

A new thalloid liverwort: Pallaviciniites sandaolingensis sp. nov. from the Middle Jurassic of Turpan–Hami Basin, NW China - Rui-Yun Li; Xue-lian Wang; Jing-Wei Chen; Sheng-Hui Deng; Zi-Xi Wang; Jun-Ling Dong; Bai-Nian Sun (PalZ, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Cotton mitogen-activated protein kinase4 (GhMPK4) confers the transgenic Arabidopsis hypersensitivity to salt and osmotic stresses - Na-Na Wang; Li–Li Zhao; Rui Lu; Yang Li; Xue-Bao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Effect of hydrogen sulfide on D1 protein in wheat under drought stress - Hua Li; Ming Quan Gao; Rui Li Xue; Dan Wang; Hui Jie Zhao (Acta Physiologiae Plantarum, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Two new flavonol glycosides from Dimocarpus longan leaves - Yongmei Xue; Wenjing Wang; Yujiao Liu; Rui Zhan; Yegao Chen (Natural Product Research, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

The association between the Lys751Gln polymorphism in the XPD gene and the risk of bladder cancer - Tianyuan Xiong; Jiqiao Yang; Haichuan Wang; Fanyi Wu; Yang Liu; Rui Xu; Zi Lv; Pei Xue; Wen Cao; Yonggang Zhang (Molecular Biology Reports, 2014)

Mechanism and comprehensive countermeasure for drought management from the view of catastrophe theory - Xiao-jun Wang; Jian-yun Zhang; Xue-wei Tong; Shahid Shamsuddin; Rui-min He; Xing-hui Xia (Natural Hazards, 2014)

An Endophytic Sanguinarine-Producing Fungus from Macleaya cordata, Fusarium proliferatum BLH51 - Xue-Jun Wang; Chang-Li Min; Mei Ge; Rui-Hua Zuo (Current Microbiology, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

How immunogenetically different are domestic pigs from wild boars: a perspective from single-nucleotide polymorphisms of 19 immunity-related candidate genes - Shanyuan Chen; Rui Gomes; Vânia Costa; Pedro Santos; Rui Charneca; Ya-ping Zhang; Xue-hong Liu; Shao-qing Wang; Pedro Bento; Jose-Luis Nunes; József Buzgó; Gyula Varga; et al. (Immunogenetics, 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Protective effect of hydrogen-rich saline on ischemia/reperfusion injury in rat skin flap - Ling Zhao; You-bin Wang; Shi-rui Qin; Xue-mei Ma; Xue-jun Sun; Ming-lian Wang; Ru-gang Zhong (Journal of Zhejiang University-SCIENCE B, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Size distributions of aerosol sulfates and nitrates in Beijing during the 2008 Olympic Games: Impacts of pollution control measures and regional transport - Xinfeng Wang; Tao Wang; Ravi Kant Pathak; Mattias Hallquist; Xiaomei Gao; Wei Nie; Likun Xue; Jian Gao; Rui Gao; Qingzhu Zhang; Wenxing Wang; Shulan Wang; et al. (Advances in Atmospheric Sciences, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Development of SSR markers for typing cultivars in the mushroom Auricularia auricula-judae - Rui Ying Zhang; Dan Dan Hu; Jin Gang Gu; Qing Xiu Hu; Xue Mei Zuo; He Xiang Wang (Mycological Progress, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Chaiqin Chengqi Decoction decreases IL-6 levels in patients with acute pancreatitis - Ling Wang; Yuan Li; Qin Ma; Yong Liu; Yuan-yi Rui; Ping Xue; Zong-guang Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Organochlorine pesticides in the soil of a karst cave in Guilin, China - Yinghui Wang; Songjun Guo; Rui Xue; Shihua Qi; Yiyin Xu; Baoming Xue; Daoxian Yuan (Environmental Monitoring and Assessment, 2011)

Risk of high-grade bleeding in patients with cancer treated with bevacizumab: a meta-analysis of randomized controlled trials - Xiao Feng Hang; Wen Sheng Xu; Jun Xue Wang; Lei Wang; Hai Guang Xin; Rui Qi Zhang; Wu Ni (European Journal of Clinical Pharmacology, 2011)

A three-dimensional finite element model of the cervical spine: an investigation of whiplash injury - Jian-Guo Zhang; Fang Wang; Rui Zhou; Qiang Xue (Medical & Biological Engineering & Computing, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

TWEAK as a target for therapy in systemic lupus erythematosus - Rui-Xue Leng; Hai-Feng Pan; Wei-Zi Qin; Chao Wang; Li-Li Chen; Jin-Hui Tao; Dong-Qing Ye (Molecular Biology Reports, 2011)

Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Analysis of the essential oil of magnolia and its effect on antioxidant enzyme activity, sCD40L and phosphorylate-activate Akt protein levels in gastric cancer mice - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Isolation and characterization of microsatellite markers from Lagerstroemia caudata (Lythraceae) and cross-amplification in other related species - Ming Cai; Rui Meng; Hui-Tang Pan; Yi-Ke Gao; Ming Sun; Ping Song; Xue-Feng Wang; Qi-Xiang Zhang (Conservation Genetics Resources, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Relationship between transmembrane signal transduction pathway and DNA repair and the mechanism after global cerebral ischemia-reperfusion in rats - Rong-Liang Xue; Jia-Xuan He; Ning Wang; Feng-Zhen Yao; Jian-Rui Lv; Gang Wu (Neuroscience Bulletin, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

AtMTM1, a novel mitochondrial protein, may be involved in activation of the manganese-containing superoxide dismutase in Arabidopsis - Zhao Su; Mao-Feng Chai; Ping-Li Lu; Rui An; Jia Chen; Xue-Chen Wang (Planta, 2007)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

Yield and quality responses of citrus (Citrus reticulate) and tea (Podocarpus fleuryi Hickel.) to compound fertilizers - Rui Wang; Xue-gen Shi; You-zhang Wei; Xiao-e Yang; Juhani Uoti (Journal of Zhejiang University-SCIENCE B, 2006)

NADK2, an Arabidopsis Chloroplastic NAD Kinase, Plays a Vital Role in Both Chlorophyll Synthesis and Chloroplast Protection - Mao-Feng Chai; Qi-Jun Chen; Rui An; Ye-Miao Chen; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)